Contribution of the Broiler Breeders’ Fecal Microbiota to the Establishment of the Eggshell Microbiota - Trudeau, Sandrine; Thibodeau, Alexandre; Côté, Jean-Charles; Gaucher, Marie-Lou; Fravalo, Philippe (Frontiers in Microbiology, 2020)
In broiler chicken production, microbial populations on the eggshell surface following oviposition are still poorly characterized, though they may significantly impact both poultry and public health. The aim of this study was to describe the microbiota of both broiler breeder hens’ feces and the surface of their eggs to assess the contribution of the parental fecal microbiota to the eggshell microbiota. A total of twelve breeder flocks in Quebec, Canada, were sampled at two different times, and a total of 940 feces and 16,400 egg surface samples were recovered. Using 16S rRNA gene sequencing, we showed that even if the microbiota of both feces and eggshells were mainly composed of the phyla Firmicutes, Actinobacteria, Proteobacteria and Bacteroidetes, the bacterial community compositions and structures differed between both types of samples. Our results also showed that both the sampling time and the flock identity significantly (p <0.05) influenced the alpha- and the beta-diversities of the studied microbiomes. Using a Venn diagram, we showed that 1790 operational taxonomic units (OTUs) were shared between feces and eggshell samples. Sequences associated with genera of potentially pathogenic and spoilage bacteria, Acinetobacter, Campylobacter, Escherichia/Shigella, Helicobacter, Listeria, Proteus, Pseudomonas, Salmonella and Staphylococcus, were shared between sample types. Interestingly some OTUs highly represented in the fecal microbiota and associated with Lactobacillus and Streptococcus genera, were absent from eggshells, suggesting a selection during the microbiota transfer and/or the potential role of environmental contamination. To the best of our knowledge, this is the first study using 16S rRNA sequencing to describe the contribution of the transfer from the fecal microbial ecosystem of laying breeder hens to the establishment of the microbiota on the surface of laid eggs, as well as the bacterial communities at both the broiler breeder feces and the eggshell levels.